Histological study of endoscopic biopsies from the lower gastrointestinal tract - Laxman Banstola; Suresh Thapa; Suresh Raj Poudel; Bhoj Raj Gautam (Journal of Pathology of Nepal)
Background: Endoscopy of the gastrointestinal tract is seen as an essential diagnostic tool because it can provide an in-depth visual assessment of gastrointestinal mucosa and allows for tissue sampling. This study aims to find out the histological diagnosis of various tissues biopsied from the lower GIT endoscopically.